Perlindungan Hukum bagi Atlet dalam Perjanjian Kontrak Kerja Berkaitan dengan Hak Kerja dalam Pasal 27 Ayat 2 UUD 1945 - Ashari Efendi; Seri Mughni Sulubara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The purpose of this research is to find out the legal protection for athletes in labor contract agreements related to employment rights in Article 27 Paragraph 2 of the 1945 Constitution. Article 27 Paragraph 2 of the 1945 Constitution reads